Case report: A case of spinal muscular atrophy in a preterm infant: risks and benefits of treatment - Nigro, Elisa; Grunebaum, Eyal; Kamath, Binita; Licht, Christoph; Malcolmson, Caroline; Jeewa, Aamir; Campbell, Craig; McMillan, Hugh; Chakraborty, Pranesh; Tarnopolsky, Mark; Gonorazky, Hernan (Frontiers in Neurology, 2023)
Spinal muscular atrophy (SMA) is a neuromuscular genetic disorder caused by loss of lower motor neurons leading to progressive muscle weakness and atrophy. With the rise of novel therapies and early diagnosis on newborn screening (NBS), the natural history of SMA has been evolving. Earlier therapeutic interventions can modify disease outcomes and improve survival. The role of treatment in infants born preterm is an important question given the importance of early intervention. Here we discuss the case of an infant born at 32 weeks who was diagnosed with SMA on NBS and was treated with Spinraza® (Nusinersen) and Zolgensma® (Onasemnogene abeparvovecxioi) within the first two months of life. With the scarce evidence that currently exists, clinicians should be aware of the efficacy and safety impact on early therapy particularly in the preterm infant.